Refractive Index Formula of Blood as a Function of Temperature and Concentration - ODUNCUOĞLU,MURAT (2021)
Abstract The analysis of blood parameters is main procedure for defining the patient’s condition. The refractive index of blood was calculated using the experimental data for a medical application and diagnostic purposes. There is small change in the refractive indices with changing with the personal conditions, illness, parasitization, temperature and others. Theoretical simulations of the refractive index of blood are difﬁcult, and it is unpredictable in different conditions. We proposed a new formula for the refractive index of blood as a function of wavelength, concentration, and temperature by using the genetic programming method. Input parameters were temperature (°C), concentration (g/L), and wavelength (nm). The refractive index values of blood were the output parameters. A total of 492 training and testing sets were selected in the spectral range of 436 to 1550 nm, in the temperature range of 20-45 °C and the concentration of 0-200 g/L HbC. The model proposes the refractive index formula blood for all the input parameters given in the range without need of extra parameters. The results are good agreement with experimental measurements in the literature and compared to Sellmeier equation.